Heparan sulfate proteoglycans mediate Aβ-induced oxidative stress and hypercontractility in cultured vascular smooth muscle cells. Issue 1 (December 2016) - Reynolds, Matthew; Singh, Itender; Azad, Tej; Holmes, Brandon; Verghese, Phillip; Dietrich, Hans; Diamond, Marc; Bu, Guojun; Han, Byung; Zipfel, Gregory
Abstract Background Substantial evidence suggests that amyloid-β (Aβ) species induce oxidative stress and cerebrovascular (CV) dysfunction in Alzheimer's disease (AD), potentially contributing to the progressive dementia of this disease. The upstream molecular pathways governing this process, however, are poorly understood. In this report, we examine the role of heparan sulfate proteoglycans (HSPG) in Aβ-induced vascular smooth muscle cell (VSMC) dysfunction in vitro. Results Our results demonstrate that pharmacological depletion of HSPG (by enzymatic degradation with active, but not heat-inactivated, heparinase) in primary human cerebral and transformed rat VSMC mitigates Aβ1-40 - and Aβ1-42 -induced oxidative stress. This inhibitory effect is specific for HSPG depletion and does not occur with pharmacological depletion of other glycosaminoglycan (GAG) family members. We also found that Aβ1-40 (but not Aβ1-42 ) causes a hypercontractile phenotype in transformed rat cerebral VSMC that likely results from a HSPG-mediated augmentation in intracellular Ca2+ activity, as both Aβ1-40 -induced VSMC hypercontractility and increased Ca2+ influx are inhibited by pharmacological HSPG depletion. Moreover, chelation of extracellular Ca2+ with ethylene glycol tetraacetic acid (EGTA) does not prevent the production of Aβ1-40 - or Aβ1-42 -mediated reactive oxygen species (ROS), suggesting that Aβ-induced ROS and VSMC hypercontractility occur through different molecular pathways. Conclusions Taken together, our data indicate that HSPG are critical mediators of Aβ-induced oxidative stress and Aβ1-40 -induced VSMC dysfunction.